Oralidade em práticas lúdicas na educação infantil - Escarião, Andréia Dutra (2019)
Thinking about an education for small children request for a careful look at the issues that engage children school, among them, the space-time of play, once the fun constitute is the structuring axis of the curriculum at this level of education. We know that play is a rights of the child, that understood as an active social subject, which is constituted through interaction, the relationships established with the culture, and the social environment in which it is inserted. Therefore, the construction of ludic spaces in pedagogical practices, which privilege orality, presents itself as a path in the search for a quality education. The interest in this study arose from the challenges surrounding the discussion, taking into account the history of neglect that marks the Child Education, specifically in relation to play, still understood as something of less importance, and educational practices that privilege written language to the detriment of oral language. In face of this context, the presente study aims to comprehend how the playfulness present in school practices helps to develop orality in children in the phase of language acquisition. The research sought to reaffirm the studies of linguistics in an interactionist perspective, the studies on the child while an active social being, constructor of culture, of the language in a multimodal perspective, and playing understood as a right of the child. For this, we search grounds of some theorists such as Marcuschi (2001), Bakhtin (1988), McNeill (2000), Kendon (1982), Kramer (2007), Vygotsky (2010), Faria (2009), also from some Documents MEC that induce public politics for Early Childhood Education, pointing the playing as the right of the child, the example the National Curriculum Referential for Early Childhood Education (1998), of the National Curriculum Guidelines for Early Childhood Education (1999), of the National Curricular Common Base (2017), among others. Methodologically, the research was accomplished with children ag group 2 and 3 years of age, enrolled in Early Childhood Education at the School of Basic Education of the UFPB. Play scenes were analyzed, recorded in different situations from the school routine. The transcripts were done through the Eudico Linguistic Annotator – Elan software for a better visualization of the data and subsequent analysis. In addition, a questionnaire was developed to be answered by the women teachers, with the intention to understand the conception about ludicity and orality and the impacts on their pedagogical practice. The analyzes pointed to the role of play as a driving force for the development of speech, proved the relevant role of story telling in this process, as also emphasize as orality as an interactive social practice, which presents itself in the form of different genres, each the school having the role of creating, based on pedagogical plans, actions that favor the use of oral language.